Film Studies in China : Selected Writings from Contemporary Cinema. - Cinema, Contemporary (Intellect Books Ltd, 2017)
"Film Studies in China is a collection of specially selected articles chosen from issues of the Contemporary Cinema journal published throughout the year. Contemporary Cinema is one of the most prestigious academic film studies journals in China. Recently, this journal has been active not only in publishing Chinese scholarship for Chinese readers but also in reaching out to academia across the globe. Film Studies in China collates the best scholarship published throughout the year in Contemporary Cinema and translates it for an English speaking readership in order to create a cross-cultural academic conversation on the fields of Chinese cinema and media studies."--Publisher description